CONTROVERSY ON THE AIRWAVES: PUBLIC DIPLOMACY, PORTRAYING AMERICA, AND PUBLIC OUTREACH THROUGH THE VOICE OF AMERICA UZBEK SERVICE - IMAMOVA, Navbahor; SCHAEFER, Richard J.; SHAFER, Richard; FREEDMAN, Eric (CENTRAL ASIA AND THE CAUCASUS, 2010)
In the United States, government-sponsored broadcast services such as Voice of America (VOA) directed to foreign audiences have been intermittently controversial, with opposing sides in the decades-long debate divided between conservative and liberal political forces. Conservatives generally hold that the U.S. should promote democracy globally and use what they consider benign propaganda techniques, including international broadcasts of news and information that is truthful, entertaining, and supportive American popular culture. Critics of VOA and other taxpayer-funded broadcasters argue that a country with a strong democratic tradition does not need to rely on “propaganda” to extend its influence. They assert that such broadcasts selectively focus on authoritarian governments that are deemed unfriendly to the U.S. or of significant strategic or economic value to U.S. interests. They also accurately note that such broadcasting is rarely directed at nations with authoritarian or dictatorial governments that cooperate with the U.S. and have military alliances or close economic ties with the U.S. In addition, liberals express concern that such broadcasts might subvert popular reform and nationalist movements that conflict with U.S. economic, strategic, or diplomatic objectives. One such example is Radio Marti, a U.S. government-funded entity that broadcasts news and entertainment to Cuba and is promoted as a means to encourage democratization, with the less clearly stated purpose of bringing down the government of Fidel and Raul Castro. Like VOA and Radio Free Europe/Radio Liberty (RFE/RL), Radio Marti is a child of the Cold War and Western anticommunism. Launched in 1983 during the Reagan administration and first on the air on 20 May, 1985, it now offers 24-hour-a-day radio short-wave and medium-wave programming. In 1990, television broadcasts to Cuba began through TV Marti. Debate continues about the effectiveness of such broadcasts. As with Radio Free Europe during the Cold War, it is difficult to measure a station’s actual audience through typical listener surveys, although efforts are made to do so. Thus, the true number of listeners and their demographics, let alone the depth and extent of their influence on audience attitudes, are speculative. There has been little academic research published about U.S. government-sponsored broadcasters.1 Among those studies, many focused-on activities during the Cold War in furtherance of democratic movements and as a counterweight to Soviet propaganda broadcasts, not on the post-Cold War period. Thus, this article reviews the history and programming of another broadcasting child of the Cold War, VOA and its Uzbek Service. It uses Uzbekistan as a case study of how one Western international broadcaster counters one authoritarian regime’s pervasive system of media controls. That history in the context of VOA’s contemporary operations provides insights regarding conflicting characterizations of the broadcaster as a largely beneficial and benevolent arm of U.S. public diplomacy or a sophisticated, subtle agent of U.S. propaganda and geopolitical aspirations.